Information Seeking Behaviour of Practicing Lawyers of Islamabad District Courts Bar Association,Pakistan - Saima Ali, Muhammad Jawwad, Pervaiz Ahmad (IJoLIS, 2024)
Purpose: This study examines the information needs and dinformation seeking behaviour of practicing lawyers of Pakistan..